2018
DOI: 10.1007/978-3-030-01887-0_32
|View full text |Cite
|
Sign up to set email alerts
|

A Series Elastic Dual-Motor Actuator Concept for Wearable Robotics

Abstract: Series Elastic Actuators (SEAs) are used extensively in the field of wearable robotics because of their energy efficiency. Redundant drivetrains enable a further reduction in electrical energy consumption, as they use the actuator's motors in a more energy efficient way. In this work, we present a Series Elastic Dual-Motor Actuator (SEDMA), a kinematically redundant actuator with series elasticity. We simulate its use in an ankle prosthesis and compare its energy efficiency to that of a traditional SEA. Result… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
7
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1

Relationship

4
1

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 8 publications
0
7
0
Order By: Relevance
“…The differential concept has been studied in [13]- [15], [25] and it is suggested that it has a great potential in reducing the energy for highly dynamical applications [23]. For example, the preliminary study in [26] has shown that the energy consumption of an active ankle and high(right) gear ratio [33].…”
Section: Kinematically Redundant Dmasmentioning
confidence: 99%
“…The differential concept has been studied in [13]- [15], [25] and it is suggested that it has a great potential in reducing the energy for highly dynamical applications [23]. For example, the preliminary study in [26] has shown that the energy consumption of an active ankle and high(right) gear ratio [33].…”
Section: Kinematically Redundant Dmasmentioning
confidence: 99%
“…The basis of our study is the kinematically redundant "Dual-Motor Actuator" (DMA) which was introduced in [24]. To create a closer match with biology, a series elastic element is added to this actuator, creating a novel concept which we coin the "Series Elastic Dual-Motor Actuator" (SEDMA) [30]. The SEDMA has tremendous potential for reducing the energy consumption of actuators performing typical human motions: simulations presented in [30] indicate that a 16% reduction in energy consumption can be achieved by replacing the series elastic actuator of an active ankle prosthesis by a SEDMA.…”
Section: Introductionmentioning
confidence: 99%
“…To create a closer match with biology, a series elastic element is added to this actuator, creating a novel concept which we coin the "Series Elastic Dual-Motor Actuator" (SEDMA) [30]. The SEDMA has tremendous potential for reducing the energy consumption of actuators performing typical human motions: simulations presented in [30] indicate that a 16% reduction in energy consumption can be achieved by replacing the series elastic actuator of an active ankle prosthesis by a SEDMA. In this work, the SEDMA's ability to perform energy-efficient bio-inspired motion is verified in hardware by implementing it in a robotic demonstrator: a robot consisting of a two-link segmented leg with actuated knee, performing low-frequency squat jumps.…”
Section: Introductionmentioning
confidence: 99%
“…have, for example, demonstrated that biomedical robots such as exoskeletons and prosthetics, can achieve high reductions in energy consumption by implementing redundant actuation concepts, especially when combined with energy buffers such as springs and flywheels [10][11][12] [13].…”
mentioning
confidence: 99%
“…In previous work, we have shown that this novel actuator concept can theoretically increase the energy efficiency of an active ankle prosthesis [13]. The proposed online controller incorporates a complete model of the actuator to calculate the actual electrical power.…”
mentioning
confidence: 99%